Numerical Evaluation of Shear Strength Enhancement in RC Beams Incorporating Various Web Opening Configurations and Pre-Stressed Fe-SMA Bar Sizes - Elkafrawy, Mohamed (2024)
Web openings in reinforced concrete (RC) beams are commonly required to accommodate utility ducts, pipes, and other service installations, optimizing space utilization and reducing construction costs. However, these openings can severely compromise the structural integrity of beams, mainly by lowering their shear strength, thus necessitating innovative reinforcement techniques to maintain their load-bearing capacity. This study presents a numerical investigation to enhance the shear strength of RC beams with various web opening shapes by integrating pre-stressed Fe-SMA (Iron-based Shape Memory Alloy) bars. The analysis focuses on two key parameters: the shape of the web openings and the diameter of the Fe-SMA bars. Finite element modeling was used to simulate RC beams with rectangular, circular, and diamond-shaped openings, and the impact of different Fe-SMA bar sizes on shear capacity was systematically evaluated. The results demonstrated that the incorporation of pre-stressed Fe-SMA bars significantly enhances the shear strength of RC beams, with the extent of improvement closely tied to both the geometry of the openings and the bar diameter. Under four-point loading, beams with diamond and circular openings exhibited fewer diagonal cracks and greater shear strength than those with square openings, especially when reinforced with larger Fe-SMA bars. Compared to the control beam (without opening), beams with diamond-shaped openings strengthened with 32 mm Fe-SMA bars showed the closest performance with only a 2% reduction in load capacity. In contrast, circular and square-shaped openings resulted in load reductions of 9.4% and 25.6%, respectively. These findings suggest that optimizing both the size of Fe-SMA bars and the shape of web openings is an effective strategy for enhancing the structural performance of RC beams with web openings.